2018
DOI: 10.1016/j.jad.2017.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Diet quality and depression risk: A systematic review and dose-response meta-analysis of prospective studies

Abstract: There is evidence that a higher quality of a diet is associated with a lower risk for the onset of depressive symptoms, but not all available results are consistent with the hypothesis that diet influences depression risk. Prospective studies that control for relevant confounders such as obesity incidence and randomized controlled prevention trials are needed to increase the validity of findings in this field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
319
6
7

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 406 publications
(367 citation statements)
references
References 76 publications
(59 reference statements)
13
319
6
7
Order By: Relevance
“…Regular exercise and improving diet quality are effective strategies for fostering good mental health and cognitive function after significant health events such as cardiac arrest. [23][24][25] However, participants in the present study did not identify such health behaviours as coping mechanisms per se. This finding has significant implications for transplant services that may not typically offer psychological support or peer mentoring programs as standard care.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Regular exercise and improving diet quality are effective strategies for fostering good mental health and cognitive function after significant health events such as cardiac arrest. [23][24][25] However, participants in the present study did not identify such health behaviours as coping mechanisms per se. This finding has significant implications for transplant services that may not typically offer psychological support or peer mentoring programs as standard care.…”
Section: Discussioncontrasting
confidence: 61%
“…Study participants indicated that before they could address their diet and exercise needs, they needed better strategies to cope with the insecurity and uncertainty associated with survival; and also needed the physical and emotional resources to deal with their current medical issues. Regular exercise and improving diet quality are effective strategies for fostering good mental health and cognitive function after significant health events such as cardiac arrest . However, participants in the present study did not identify such health behaviours as coping mechanisms per se .…”
Section: Discussioncontrasting
confidence: 60%
“…However, previous research has demonstrated that several variables could buffer these negative consequences of chronic stress on mood, demonstrating that diet is closely related to allostatic load [34,35]. In this regard, recent reviews and meta-analyses have demonstrated that a high-quality diet is associated with a lower risk of depressive symptoms [36,37,38]. There are a number of biological pathways that could explain that adolescents who maintain a high-quality diet could buffer the consequences of derived stress from bullying, reducing the risk of suffer depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of biological pathways that could explain that adolescents who maintain a high-quality diet could buffer the consequences of derived stress from bullying, reducing the risk of suffer depressive symptoms. The dietary intake of folate, zinc, and magnesium typical of a healthy dietary pattern, such as the MD, or the reduction of systemic inflammation, oxidative stress, and adaptive brain development could be on the basis of the protective effect of adequate dietary habits in chronically-stressed adolescents [36,37,38,39,40]. These mechanisms could explain the obtained results in the present study, in which individuals with healthy dietary habits suffer from lower levels of depression, although they also suffer from high levels of bullying.…”
Section: Discussionmentioning
confidence: 99%
“…Benefits of physical activity are well documented (Schuch et al, 2018;Stubbs et al, 2018;Teychenne, Ball, & Salmon, 2008). In addition, a growing body of evidence has highlighted the influence of dietary factors on symptoms of depression (Molendijk, Molero, Ortuno Sanchez-Pedreno, Van der Does, & Angel Martinez-Gonzalez, 2018). One commonly consumed foodstuff postulated to have moodenhancing properties is chocolate.…”
Section: Introductionmentioning
confidence: 99%